Epistimologi Kekerasan Seksual Dalam Hak Ijbâr Wali Menurut Analisis Gender - Nabil, Muhammad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
The emergence of planning for a law on the elimination of violence against women or the PKS Bill has drawn a lot of criticism, both for and against. In the PKS Bill, article 11 paragraph 2 letter f states that forced marriage is a criminal act of sexual violence. However, quite a few cases of divorce are caused by an influence on the guardian's right to ijbar. Responding to this, this research raises at least two basic questions, namely what is the epistemology of sexual violence according to gender analysis and how the right to ijbâr can trigger the roots of sexual violence. From the results of this research, the right to ijbar does not appear to be the root of sexual violence unless there is an element of coercion (ikrah). Although in the view of madzhab jurisprudence there are also pros and cons regarding the existence of ijbar. This occurs because a child is mature in choosing a mate so that the guardian only acts as the legalizer of the marriage. An approach with a gender theme can explain the roots of sexual violence that occurs in the right to ijbar which is interpreted as ikrah (coercion) and discrimination that occurs against women from related topics.